Analysis of Problems Collecting Zakat Funds in Zakat Amil Institution (LAZ) Yogyakarta Special Region - Neli Rahma Wanti (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
As a province with a majority Muslim population, the Yogyakarta Special Region plays an active role in collecting, managing, and distributing zakat funds to alleviate poverty. However, the amount of zakat funds collected is not commensurate with its potential. This research aims to analyze priority problems, solutions, and strategies in the problem of optimizing the collection of zakat funds carried out by the Amil Zakat Institution (LAZ) in DIY from various aspects. This research uses a mixed method type of research which combines qualitative and quantitative research with data analysis techniques using the Analytic Network Process (ANP) method with the help of Super Decisions software. The data sources in this research are primary data and secondary data which include interviews, questionnaire distribution, and document techniques. Sampling in this study used a purposive sampling method by taking six informants consisting of one expert and five zakat practitioners in DIY to formulate priorities in the problem areas, solutions, and strategies for three aspects, namely government, LAZ, and society. The research results show that the priority problem from the government aspect is grand design or strategic planning. Meanwhile, the priority problem in the LAZ aspect is the professionalization of LAZ and the priority problem in society is community intensity. The priority solutions from the government, LAZ, and community aspects are, respectively, standardization of reporting, promotion, and socialization of zakat, and public knowledge. The strategic priorities that need to be carried out sequentially are regulations, facilities, and institutional standardization. This research shows that there is a need for regional regulations governing zakat in DIY, improving amil performance, and increasing public knowledge about zakat.